2017
DOI: 10.1038/s41598-017-13880-5
|View full text |Cite
|
Sign up to set email alerts
|

A Novel β-adaptin/c-Myc Complex Formation Modulated by Oxidative Stress in the Control of the Cell Cycle in Macrophages and its Implication in Atherogenesis

Abstract: Our study tested the proposal that c-Myc activation in macrophages is differentially carried out dependent on the intracellular oxidative state of cells and potentially associated to the process of atherogenesis. Under our experimental conditions, the generation of reactive oxygen species carried out by the presence of oxidized low density lipoproteins (oxLDL) or Gram negative bacterial lipopolysaccharides (LPS) modifies the expression of cellular adhesion molecules such as c-Abl, calcium transport proteins su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
5
11
0
Order By: Relevance
“…The specific case of the cytotoxicity exerted by Tum may be associated with an alteration in the nuclear structure (Figure 5F), considering the involvement of Lamin-B, a similar phenomenon that we have described in macrophages treated with LPS [36]. It should be noted that our group has described the function of new protein complexes formed by the adapter protein β-adaptin and transcriptional activators such as c-Myc and c-Jun that regulate the cell cycle and mechanisms such as endocytosis [36]. This condition was found to be affected in the nucleus under the stimuli with PA and Tum (Figure 5G), which we have correlated with the presence of an oxidative imbalance [37] implicating critical functions in the cells.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The specific case of the cytotoxicity exerted by Tum may be associated with an alteration in the nuclear structure (Figure 5F), considering the involvement of Lamin-B, a similar phenomenon that we have described in macrophages treated with LPS [36]. It should be noted that our group has described the function of new protein complexes formed by the adapter protein β-adaptin and transcriptional activators such as c-Myc and c-Jun that regulate the cell cycle and mechanisms such as endocytosis [36]. This condition was found to be affected in the nucleus under the stimuli with PA and Tum (Figure 5G), which we have correlated with the presence of an oxidative imbalance [37] implicating critical functions in the cells.…”
Section: Resultssupporting
confidence: 68%
“…Expanding the characterization of this phenomenon, we found that stimulation with PA and LPS promotes the formation of RNS in the extracellular medium (Figure 6A). In a previous publication, we correlated the formation of RNS with the oxidative damage phenomenon and UPR activation in macrophages treated with LPS [36]. In our conditions, a drastic drop in insulin release was observed upon the treatment with palmitic acid and LPS (Figure 6B), associated with an increase in RNS formation in the culture medium.…”
Section: Resultssupporting
confidence: 67%
“…An effect was also observed on β-adaptin, whose new moonlighting function we have described previously as adapter protein of endocytosis and regulator of cell cycle through c-Myc interaction. 17 In our conditions the treatment with Cry prevents the reduction in its expression. Likewise, Cry inhibits the expression of COX-2 (Figure 3F).…”
Section: Cry Modulates the Perk Pathway Under Tum-induced Er Stressmentioning
confidence: 68%
“…Then, solution was adjusted to a density solution of 1.053 g/mL and centrifuged 90,000 rpm for 3 h. The dil-LDL fraction was recovered and dialyzed to PBS. Protein determination was performed and dil-LDL was employed in hepatocyte experimentation ( 29 ).…”
Section: Methodsmentioning
confidence: 99%